A Comparative Study of the Photodegradation of Two Series of Cyclic Olefin Copolymers. (13th July 2017) - Gutiérrez-Villarreal, Mario H.; Zavala-Betancourt, Sara A.
Abstract : A series of commercial cyclic olefin copolymers (COC), namely, ethylene-norbornene (E-NB) and ethylene-tetracyclododecene (E-TD), were processed as thin films with thicknesses of 25 μ m by an extrusion process. The photodegradation of neat and formulated films with different metal stearates (Fe, Co, and Mn) was investigated using an ultraviolet (UV) light lamp (340 nm) for a period of 30 days in an accelerated weathering tester model QUV from Q-LAB according to the ASTM D 5208-01 standard practice. Changes in carbonyl index (CI) and tensile properties were used to evaluate the photodegradation of the films and other properties, such as T g variation by DSC, were also analyzed. The present study reveals that (E-NB) copolymers show higher sensitivity to photodegradation than (E-TD) resins, in the absence and presence of metal stearates. We also find that the Fe salt shows the highest oxidative activity.